Incidence and risk factors for tuberculosis among people living with HIV in Bangui: A cohort study - Jean De Dieu Longo; Sylvain Honoré Woromogo; Henri Saint-Calvaire Diemer; Gaspard Tékpa; Laurent Belec; Gérard Grésenguet (Elsevier, 2022)
Objectives: The objectives of this study were to determine the incidence and risk factors of tuberculosis (TB) among people living with HIV (PLHIV). Methods: A cohort study was carried out in an HIV infection management centre in Bangui. PLHIV aged 18 or older, with no history of TB, enrolled between January 1, 2017 and December 31, 2018 were included in the study. The chi-square test was used only to compare the proportions at the 5% significance level. To determine the risk factors, we used the Cox regression adjusted hazard ratio, using Epi Info 7 software. Results: A total of 677 patients including 618 (91.28%) on antiretroviral therapy were included in the study. The median age was 34 with extremes ranging from 18 to 57. Of the patients followed, 104 developed TB. The overall incidence of TB was 15.37 (104/677) cases per 100 PLHIV-years. This incidence was 13.10 (81/618) cases per 100 in patients on ART-years and 38.99 (23/59) cases per 100 patients on pre-ART-years. In pre-ART patients the incidence of TB was therefore almost 3 times higher than that of PLHIV on ART (p = 0.03). WHO clinical stages III and IV (p = 0.02), absence of ART (p = 0.03), poor adherence (p = 0.004) and low functional capacity (p = 0.04) were the risk factors associated with the occurrence of TB among PLHIV in Bangui. Conclusions: The high incidence of TB in our context is essentially linked to delay in diagnosis and the quality of care. Early initiation of antiretroviral therapy, systematic screening for TB in PLHIV upon entry into the active queue and better monitoring of patients on ART are strongly recommended.